Efektivitas Penggunaan Subsidi Kuota Internet Mahasiswa IAIN Ponorogo Di Masa Pandemi Covid-19 - Muthoharoh, Siti Lu’lu’il Maknun (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) STIB Banyuwangi, 2021)
Corona Virus Disease 2019 or abbreviated as Covid-19 is a dangerous disease that is transmitted through air or indirect contact. Covid-19 in Indonesia has been going on for a long time, that is, it has reached more than a year. The impact caused by Covid-19 also covers overall human activities, both for parents, workers, students, as well as children and toddlers. Due to the easy spread of Covid-19, namely through the air and various media that have been exposed to positive Covid-19 patients, the government has imposed social and regional restrictions. This causes all activities in the community to be carried out indirectly or online from home. The world of education is no exception, which is one of the many things affected by Covid-19. Educational institutions both in the form of schools and colleges have begun to apply learning rules through online media from home. To support this learning program, the government provides a lot of assistance, both in the form of cutting school fees to providing subsidized assistance in the form of internet quotas. Here the authors conducted a study in which to find out how effective the use of internet quota subsidies was by students during the Covid-19 pandemic. This research uses a qualitative method obtained from the results of a case study that focuses on assistance provided by the government in efforts to reduce the impact caused by Covid-19. The results of the study explained that the provision of assistance in the form of internet quotas by the government to students was not very effective in its distribution and use. This is due to several determinants as some regions cannot use it due to weak signal constraints.